İki Dönüştürücülü Ultrasonik Temizleme Sistemi Tasarımı - Şahin, Mehmet Emin (Fen Bilimleri Enstitüsü, 2014)
Hızla artan dünya nüfusu, plansız üretim, sanayileşme ve sağlıksız kentleşme, nükleer denemeler, bölgesel savaşlar, verimi artırmak amacıyla kullanılan tarım ilaçları, yapay gübreler ve deterjan gibi kimyasal maddelerin kullanımı çevre kirliliğine yol açarak çevre sorunlarının ortaya çıkmasına sebep olmaktadır. Bunun neticesinde kirlenen hava, su ve toprak canlıların yaşamını olumsuz etkileyecek boyutlara ulaşmıştır. Yapılan araştırmalar dünyadaki mevcut çevre kirliliğinin %50 ‘sinin, son 35 yılda meydana geldiğini ortaya koymaktadır [19]. Dünya üzerindeki yaşamın kaynağı olan ve dolayısı ile insanoğlunun da yaşamak için muhtaç olduğu su üzerinde ciddi boyutlarda kirlenmeye sebep verebilen deterjanlar,  kimyasallar, asit bazlı temizleyiciler doğrudan olduğu gibi dolaylı yoldan da çevreye büyük boyutlarda zarar verebilme potansiyeline sahiptir. Deterjanlar sudaki mikro habitatın yok olmasına neden olabileceği gibi, bazı yaşam formlarının aşırı miktarda üreyerek doğal ekolojik sistemin zarar görmesine de neden olabilir.  Bahse konu sebeplerden ötürü son yıllarda temizlik endüstrisinde su ve petrol temelli temizleyicilerin yanında doğaya dost alternatif temizleme teknikleri geliştirilmeye çalışılmıştır. Bununla beraber, endüstride üretilen parçaların çeşitliliği, hassasiyeti ve kalitesi göz önüne alındığında temizlik talepleri çeşitlenerek artmaktadır. Günümüz endüstrisinde, artan temizlik taleplerini karşılamak amacıyla pek çok araştırmalar yapılmış ve ultrasonik temizleme yöntemi de oldukça gelişme göstermiştir. Ultrasonik temizlik genellikle hassas temizlemelerde, hızlı, ucuz, güvenilir ve daha kaliteli temizlik sağladığı için kimyasal temizliğe alternatif olarak kullanılır. Ultrasonik temizleme ilk olarak RCA (Radio Corporation of America) firmasının araştırma laboratuarında bulunmuştur. Freon gazı kullanılarak gerçekleştirilen soğutma işleminde 300kHz frekansta çalışan kristalin etrafında dalga hareketinin çıktığı tesadüfen fark edilmiştir. Bu dalga hareketinin ultrasonik temizleme metodu olarak kullanılabileceği uzun bir süre fark edilememiştir[4, 20]. Günümüzde kullanılan ve büyük çoğunluğunun 18kHz-40kHz arasında çalıştığı ultrasonik temizleme sistemleri 1950’li yılların sonlarında geliştirilmeye başlanmıştır.  Ultrasonik temizleme sistemleri genel olarak dört esas birimden oluşur. Bunlar paslanmaz çelikten yapılmış bir kazan, kazanın alt veya yan yüzeyine özel bir yapıştırıcı ile yapıştırılmış bir veya birden fazla ultrasonik dönüştürücü, ultrasonik üreteç devresi ve temizleme sıvısıdır. Uygun frekans ve güç değerlerinde sürülen ultrasonik dönüştürücünün ürettiği ses ötesi dalgalar temizleme kazanındaki sıvıda alçak ve yüksek basınç bölgeleri oluştururlar. Bu farklı basınç bölgeleri sıvı içerisinde yüksek miktarda mikroskobik kabarcıklar üretirler. Bu kabarcıklar alçak basınçta genişleyerek büyürken yüksek basınçta büzülerek şiddetli bir biçimde patlar.  Bu olay literatürde ses ötesi kavitasyon olarak adlandırılır ve ultrasonik temizlemenin temelini oluşturur.  Bu tez çalışması kapsamında 38kHz’lik iki adet ultrasonik dönüştürücüye sahip mikrodenetleyici tabanlı geliştirilmiş farklı sürme tekniklerine sahip bir ultrasonik temizleme sistemi tasarlanmıştır. Kontrol ve sürme devresi olarak ATmega-628 mikrodenetleyicisini kullanan Arduino programlama kartı kullanılmıştır. C programlama dilinin kullanılması ile birlikte bu kartın avantajlarından maksimum seviyede faydalanılması ve yüksek hassasiyette sürme gerçekleştirilmesi amacıyla gerekli görülen kısımlarda Assembly programlama dili kullanılmıştır.  Gerçekleştirilen yazılım ile ultrasonik temizleme sistemi üç esas sürme tekniğini kullanmak üzere programlanmıştır. Bunlardan birincisi olan sabit frekansta sürme metodu için 35,5kHz ve 41.5kHz frekans aralığında yüksek hassasiyetli 67 adet sabit frekans değerinde istenen sıcaklıkta ve sürede temizleme gerçekleştirilebilmektedir. İkinci çalışma metodu olarak süpürmeli frekans metodu programlanmıştır; bu çalışma metodunda rezonans frekansı civarında set edilen frekans bandı aralığında sürme frekansı çok küçük adımlar ile azaltılıp artırılarak taramalı olarak temizleme gerçekleştirilmiştir. Gerçekleştirilen üçüncü ve son sürme tekniği ise faz farklı sürme metodudur. Bu çalışma metodunda iki adet ultrasonik kristal rezonans frekansında faz farklı olarak sürülmektedir. Söz gelimi 180º faz farkında birinci kristal 300V gerilim altında iken ikinci kristal 0V gerilim altındadır. Bu çalışma metodu literatürde henüz mevcut değildir. Gerçekleştirilen program ile 0-180º arası faz farkı değerlerinde iki kristal sürülebilmektedir. Bunların yanı sıra sıvı sıcaklığı ölçülerek 20-80ºC arası istenen sıcaklıkta temizleme gerçekleştirilebilmektedir. Gerçekleştirilen ultrasonik temizleme sistemi kullanılarak temizleme etkinliğinin frekans, faz farkı, sıcaklık gibi çeşitli parametrelere göre değişiminin incelenmesi amaçlandığından, 38kHz’lik çalışma frekansında gelişmiş kontrol özelliklerine sahip bir ultrasonik üreteç devresinin sürücü ve güç kartı devre tasarımları gerçekleştirilmiştir. Böylece ultrasonik dönüştürücünün sürülmesinde tepeden tepeye genliği 300V olan modüle edilmiş sinyaller üretilmiştir. Bu amaçla yüksek gerilim değerlerinde çalışan güç mosfetleri kullanılmıştır. Ayrıca sistem üzerindeki alçak ve yüksek gerilimler optokuplörlü devreler ile birbirinden izole edilmiştir. Ultrasonik dönüştürücünün doğru güç ve frekans değerlerinde sürülebilmesi ve neticesinde maksimum güç aktarımının gerçekleşmesi temizleme etkinliği için çok önemli bir parametredir. Zira doğru modellenen ve rezonans frekansında sürülen piezo-elektrik dönüştürücüler üreteç devresi ile harmoni içerisinde maksimum titreşim sağlarlar[8]. Bu sebeple ultrasonik dönüştürücüler için literatürde kullanılan en temel eşdeğer devre olan Butterworth – Van Dyke Transducer Model [16] kullanılarak dönüştürücü modellenmiştir. Bununla birlikte, IM3570 (Empedans Analizörü) kullanılarak değişen sıvı seviyelerine rezonans frekansının değişimi incelenmiştir. Gerçeklenen ultrasonik temizleme sisteminde temizleme etkinliğinin incelenmesi amacıyla literatürde yaygın olarak kullanılan folyo testi yöntemi kullanılmıştır. Zira dikey olarak kazana daldırılan aliminyum folyo kazanda oluşan kavitasyon patlamalarının gücü ve bölgeselliği nispetinde aşınır. Devamında bu aşınmaların analiz edilmesi amacıyla Tunç. C. [4] tarafında geliştirilen MATLAB tabanlı görüntü işleme programı kulllanılmıştır. Bu sayede temizlemenin etkinliği ve homojenliğini incelenmek amacıyla folyo üzerindeki aşınmış bölgelerin toplam alanları, standart sapma değerleri, merkez nokdasına olan uzaklıkları gibi çeşitli parametreler kullanılarak sonuçlar analiz edilmiştir. Bu tez çalışması kapsamında gerçeklenen temizleme sisteminde yeni bir sürme metodu olarak faz farklı sürme metodu gerçekleştirilmiş ve temizleme üzerindeki etkileri incelenmiştir. Netice olarak temizlemenin veriminin yeni önerilen metot ile %25’e kadar artırılabildiği görülmüştür. Sonuç olarak hangi sıcaklık değerinde hangi sürme metodunun kullanılması gerektiği bilgisine ulaşılmıştır. Son olarak tez raporunda, ultrasonik temizleme sisteminin tasarım aşamaları, ultrasonik dalgaların doğası ve ultrasonik temizleme konularına da yer verilmiştir.

Raising of the human population rapidly, unplanned production, industrialization and improper urbanization, nuclear experiments and wars those affect the surroundings very close, agricultural chemicals which are used to improve the production, artificial fertilizers and chemicals that can destroy the nature of the earth such as detergent, etc. are all the reasons of the pollution. As a result of this unconscious usage of these chemicals, the natural environment (such as oceans, earth, atmosphere, etc.) and all living creatures are affected in a negative aspect. The latest researches emphasize that the 50% of the current pollution is caused in the last 35 years [19]. It’s a common knowledge that the water is the core of human life. Therefore, human beings are in need of clean water resources. However, all the chemicals such as detergent, acid based cleaners have the big potential to damage the nature directly and even indirectly. Additionally, detergents can cause to destroy the micro habitats in the water, besides they can also be the reason of the exceeding reproduction of some creature, which can lead unbalanced ecologic system.  Due to these reasons, in recent years, chemist are getting eager to invent some cleaners which are not harmful for the nature as the chemicals based on petroleum and water. Additionally, diversity of the equipment productions and their sensitivity are in an increasing manner. When we consider this increase, people tend to have all the new produced equipment. In today’s technology, in order to respond all these demands, scientist made many researches and experiments, so ultrasonic cleaning technology also improved reasonably. Ultrasonic cleaning is usually used for sensitive cleanings. It has some advantages such as faster, cheaper, more reliable and has more quality than conventional chemical cleaning. The history of ultrasonic cleaning begins more than 80 years ago, to the early 1930s. Ultrasonic cleaning technique was first held in the research laboratories of RCA (Radio Corporation of America) company, located in New Jersey, in USA. They made a cooling experiment with Freon gas and with a crystal. While they were in the process of the experiment, they discovered that there is a wave movement around the crystal. But no one had an idea to use this wave movement as a magnificent way of cleaning [4, 20]. The majority of ultrasonic cleaning systems, which were developed later in the 1950s, are operated at 18kHz to 40kHz. Although 18kHz is the lowest frequency, it is still being used routinely in industry. On the other hand, a 6kHz system was developed in Russia but short lived. Up to the late 1980s most of commercial cleaning systems are operated at 25kHz to 40kHz. Ultrasonic cleaning systems mainly have 4 items. These items are one large tank which must be made of stainless steel, couple of ultrasonic transducers which are attached under or on the sides of the tank by using a special kind of glue with high ultrasonic conductivity, electrical generator for the transducers and cleaning liquid. By using an electrical signal generator that produces a high frequency signal (20 to 200 kHz), the transducer rapidly transmits ultrasound waves into the liquid. Those waves cause high and low pressure areas. During the low pressure cycle, the liquid is torn apart and this action creates a vacuum cavity within the liquid. These cavities will get bigger and later smaller with the continuity of the ultrasound waves coming from the source. When each single bubble reaches a certain size (with respect to the frequency and the power of the signal) the bubble can no longer retain its shape. The bubble will explode violently and creates a temperature up to 5000 degrees centigrade and a jet of plasma that impacts against whatever object is in the tank. In the big scene of the frame, millions of bubbles will be created and have the same process of exploding. This is known as ultrasound cavitation in the literature and is the basis of ultrasonic cleaning systems. In this study, the design of an ultrasonic cleaning machine which is microcontroller based and has different drive techniques is achieved. The system contains two ultrasonic transducers with 38 kHz resonance frequency. As the control and drive circuit, ATmega-628 microcontroller based Arduino card is used. C programming language is used in this study, but in some cases assembly programming language is preferred, as well in order to make more sensitive control and drive and also to take advantage of Arduino. The developed ultrasonic cleaning system is programmed to have three main drive techniques. The first technique is to drive the transducers with a certain frequency. In this method, one can achieve cleaning in a desired temperature and time with 67 different high sensitive frequency pulses which are produced between 35.5 kHz and 41.5 kHz. The second technique is making the cleaning with a sweeping frequency pattern. The system is programmed in this way and the resonance frequency is the basis for this system. A band is set around this resonance frequency and the system starts to sweep this band with very small frequency steps. So the cleaning is achieved with the sweeping frequency technique. When it comes to the third technique, it can be defined as phase different driven technique. In this technique, two crystals are driven with the same resonance frequency but have phase difference between. For instance, when they have 180 degrees of phase difference, the first crystal is supplied with a 300V source while the remaining one is grounded and vice versa. The last operational method isn’t common/exists in the literature yet. In order to tell more details about the last method, user can set the phase difference between 0-180 degrees with the developed program, so two transducers will be driven with two different phases. In addition, liquid temperature is measured and if necessary, it’s heated till the desired temperature between 20-80 degrees Celsius.  In this design, it’s aimed to investigate the effects of frequency, phase difference and temperature on ultrasonic cleaning efficiency. For this reason, an ultrasonic driver and power units of a microcontroller based ultrasonic generator, which has advanced controlling functions around resonance frequency of 38 kHz, is designed and implemented. Thus, modulated 300V peak to peak voltage signals are generated in order to drive the transducers. Due to the necessity of high voltage, power mosfets with fast switching capability are used. Moreover, in the circuit design, high and low voltage stages are isolated from each other with optocoupler circuits. In order to achieve an efficient cleaning, the power and the frequency of the electrical signal should be chosen properly and after that maximum power translation should be carried over the transducers. Those parameters are vital, because if the piezo-electric transducers are modeled and driven in the resonance frequency, they will provide maximum vibration with generator circuits, accordingly. Thereby, Butterworth – Van Dyke Transducer Model [16], which is the most common equivalent circuit model characterizing for a piezoelectric transducer near the resonant frequency, is used in modeling of the design. This model is often adapted to model electromechanical resonance characteristics of crystal oscillators [16]. Furthermore, when a piezoelectric transducer is mounted to a mechanical structure or  when the cleaning tank is filled with liquid, the mechanical boundary conditions of the piezoelectric transducers change, and accordingly, resonant frequency of the system changes. To identify and follow that frequency under different conditions, IM3570 (Impedance Analyzer) is used for measurements. So the effect of the liquid level over the resonance frequency of transducer is investigated and the chart of resonant frequency versus different loads is graphed. In order to analyze the effectiveness of an ultrasonic cleaning system, foil test is the most common and practical method of indicating the power and the washing profile in cleaning tank. Therefore, foil test technique is used to analyze the efficiency of the designed cleaning system with respect to different parameters mentioned before. In this method, foil is immersed into the tank vertically or horizontally and with respect to the power and distribution of cavitation bubbles, it’s eroded. As the cleaning goes on, the erosion turns into holes on the foil. And the shape, amount and distribution of these holes shows the cleaning profile  and cavitation density of bubbles.  Following that, to analyze the results of foil tests, an image processing MATLAB program which is developed by Tunç C[4] is used. With the program, the holes’ areas on the foil, their standard deviation and their distance to the center are used to estimate the efficiency and homogeneity of cleaning. Firstly, in order to calculate the parameters above, the scanned image of cleaned foil is converted to a 8-bit image with black, white and gray-tone colors. In the converted image, 0 means white while 255 means black. The value of 160 is used as the threshold value to analyze the converted image. In this thesis, a new cleaning method which we can define as phase difference technique is developed and proposed, too. The effects of this new method on cleaning efficiency are also examined. As a result of this method, the cleaning efficiency is improved about 25% of the conventional techniques. Additionally, examination of the cleaning efficiency with respect to various parameters has been identified and specific methods for specific temperatures are defined for the designed system.  Finally, in this thesis report, ultrasonic cleaning phenomena, design steps of the ultrasonic cleaning machine, definition and nature of ultrasonic waves, and foil test results are included.
Desing And Analysis Of An Ultrasonic Cleaning System With Two Transducers
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2014
Keywords: Ultrasonic Temizleme; Piezoelektrik Dönüştürücüler; Ultrasonic Cleaning; Piezoelectric Transducers